The human capital selection of young males seeking asylum in Germany - Martin Lange; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
This study analyses the selection of recently arrived asylum seekers from Middle Eastern and African countries in Germany. The findings suggest that, on average, asylum seekers have 22 percent more years of schooling - the indicator used for human capital - when compared to same-aged persons from their country of origin. In addition, it is shown that asylum seekers in the sample often accumulated rather low or relatively high levels of schooling compared to same-aged persons in their countries of origin. This phenomenon is even more pronounced for parental education. It is demonstrated that the indicators of individual and parental human capital influence short-run integration outcomes in Germany, while work experience in the home country does not. The paper discusses potential economic explanations for the findings on immigrant selection and integration outcomes.
Keywords: F22; J15; J24; 330; immigrant selection; asylum seekers; human capital; family background; integration